Family Portraiture in 18th Century Russia and All-European Artistic Heritage - Kolmogorova, Ekaterina E. (Actual Problems of Theory and History of Art, 2025)
The article discusses the influence of all-European artistic heritage including the Renaissance on the development of family portraiture of 18th century Russia. This theme has not been a subject of special research yet. Therefore, the paper aims to research how the family portrait tradition that developed in Western Europe has been perceived in Russia in typological, figurative, compositional, and symbolic contexts. In order to achieve the goal, we conducted a complex comparative analysis of several paired, twin, and group family portraits created by different Western European schools since the Renaissance and the ones painted in 18th century Russia. We paid special attention to the ways of integration of the Western traditions into Russian family portraiture. The analysis shows that the family portrait typology per se, as well as the artistic means, compositional techniques, and family attributes widely applied in the West, influenced Russian family portraiture; but at the same time, this European tradition was deeply spiritualized by the unique Russian identity.
Keywords: portrait; family portrait; European family portrait; 18th century Russian painting; European painting; family representation in portraiture; all-European artistic heritage; history of the family portrait